Research Note—Investigating the Influence of the Functional Mechanisms of Online Product Presentations - Jiang, Zhenhui; Benbasat, Izak (Information Systems Research, 2007)
Internet-based interactive multimedia technologies enable online firms to employ a variety of formats to present and promote their products: They can use pictures, videos, and sounds to depict products, as well as give consumers the opportunity to try out products virtually. Despite the several previous endeavors that studied the effects of different product presentation formats, the functional mechanisms underlying these presentation methods have not been investigated in a comprehensive way. This paper investigates a model showing how these functional mechanisms (namely, vividness and interactivity) influence consumers' intentions to return to a website and their intentions to purchase products. A study conducted to test this model has largely confirmed our expectations: (1) both vividness and interactivity of product presentations are the primary design features that influence the efficacy of the presentations; (2) consumers' perceptions of the diagnosticity of websites, their perceptions of the compatibility between online shopping and physical shopping, and their shopping enjoyment derived from a particular online shopping experience jointly influence consumers' attitudes toward shopping at a website; and (3) both consumers' attitudes toward products and their attitudes toward shopping at a website contribute to their intentions to purchase the products displayed on the website.